Using Cross Puzzles to Improve Maharah Kitab on Students at the Al-Ihsan Foundation, Medan - Yushinta Novia Nur Fatikah; Akmal Walad Ahkas (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study was structured with the aim of improving students' writing skills using Crossword Puzzle (TTS) media for class VIII students at the Al-Ihsan Foundation, Medan, North Sumatra for the 2021/2022 academic year. This type of research is Classroom Action Research (CAR). This research was conducted in the even semester of the 2021/2022 Academic Year, namely in April-May. The research subjects were students of class VIII of the Al-Ihsan Foundation which consisted of 33 students. The object of research is the students' writing ability. Research data were collected using a test given to each student. Based on the results of the percentage of student learning tests in the first cycle was 76.96% and in the second cycle increased to 88.03%. From the comparison of the two cycles, there was an increase of 11.07%. From the comparison of the two cycles, there is an increase, this means that writing skills (maharah kitabah) using the Crossword Puzzle (TTS) media have increased.